2017
DOI: 10.1177/1069072717723096
|View full text |Cite
|
Sign up to set email alerts
|

Dualistic Passion for Work and Its Impact on Career Outcomes

Abstract: Drawing on the dualistic model of passion, we conducted a construct validation of the passion for work scale across four samples of employees and students. Specifically, we tested the two-factor structure of the model and examined the convergent, discriminant, and criterion validity of passion for work against conceptually similar work motivation and career-relevant constructs. Findings support the duality of the passion for work (i.e., harmonious and obsessive), its uniqueness as a motivational work construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 75 publications
1
53
0
1
Order By: Relevance
“…Passion does resemble various other motivational constructs in terms of time and energy exerted, liking, and meaningfulness of the passionate activity. Nevertheless, harmonious and obsessive passion display discriminant validity from work-related constructs such as work involvement, engagement, goal orientation, calling, and workaholism (Lajom et al, 2018). Passion is conceptually distinguished from these other motivational processes by its duality, its cognitive internalization of the career into the self, and its strong affective liking for the work itself (Ho and Astakhova, 2018).…”
Section: Passions and Resourcingmentioning
confidence: 99%
“…Passion does resemble various other motivational constructs in terms of time and energy exerted, liking, and meaningfulness of the passionate activity. Nevertheless, harmonious and obsessive passion display discriminant validity from work-related constructs such as work involvement, engagement, goal orientation, calling, and workaholism (Lajom et al, 2018). Passion is conceptually distinguished from these other motivational processes by its duality, its cognitive internalization of the career into the self, and its strong affective liking for the work itself (Ho and Astakhova, 2018).…”
Section: Passions and Resourcingmentioning
confidence: 99%
“…Interestingly, mixed results regarding the relationship between perceiving a calling and workaholism have been reported. Duffy and colleagues [6] reported no significant relationship between the two variables, while Lajom et al [7] found a negative but nonsignificant relationship between them. In contrast, Hirschi and colleagues [35] found a small but positively significant relationship between calling and workaholism.…”
Section: Calling and Hwimentioning
confidence: 94%
“…Second, we also posited that OP could mediate a positive relationship between perceiving a calling and workaholism. According to previous research [7,41], OP and workaholism are closely related but are distinguished psychological constructs; they share core characteristics (e.g., being obsessed about work). The link between perceiving a calling and OP can be explained by the fact that individuals who endorse a calling consider their work as a core part of their identities [42].…”
Section: Mediating Role Of Passionmentioning
confidence: 98%
See 1 more Smart Citation
“…Work passion is also related to calling (Lajom et al, 2018). Both constructs refer to activities that people love, are regularly engaged in, and that define their identity.…”
Section: Passion For Workmentioning
confidence: 99%